Solve the following system of ODE
(48D+4)y - (2D+1)z = e
-x
(D+8)y - 3z = 5e
-x
; D =d/dx
Solve the following system of ODE
(48D+4)y - (2D+1)z = e
-x
(D+8)y - 3z = 5e
-x
; D =d/dx
"\\begin{cases}\n 48\\frac{dy}{dx}+4y-2\\frac{dz}{dx}-z=e^{-x} \\\\\n \\frac{dy}{dx}+8y-3z=5e^{-x} \n\\end{cases}"
Solution:
From second equation:
"z=\\frac13(\\frac{dy}{dx}+8y-5e^{-x} )" (*)
"\\frac{dz}{dx}=\\frac13(\\frac{d^2y}{dx^2}+8\\frac{dy}{dx}+5e^{-x})"
Substitute "z" and "\\frac{dz}{dx}" into the first equation:
"48\\frac{dy}{dx}+4y-\\frac23(\\frac{d^2y}{dx^2}+8\\frac{dy}{dx}+5e^{-x})-\\frac13(\\frac{dy}{dx}+8y-5e^{-x} )=e^{-x}"
"-\\frac23\\frac{d^2y}{dx^2}+\\frac{127}{3}\\frac{dy}{dx}+\\frac43y=\\frac83e^{-x}"
"2\\frac{d^2y}{dx^2}-127\\frac{dy}{dx}-4y=-8e^{-x}" (**)
First find the general solution of the corresponding homogeneous equation:
"2\\frac{d^2y_0}{dx^2}-127\\frac{dy_0}{dx}-4y_0=0"
Let's compose and solve the characteristic equation:
"2\\lambda^2-127\\lambda-4=0"
"\\lambda_1=\\frac{127-\\sqrt{16161}}{4}" , "\\lambda_2=\\frac{127+\\sqrt{16161}}{4}" .
"y_0=C_1e^{\\lambda_1x}+C_2e^{\\lambda_2x}=C_1e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2e^{\\frac{127+\\sqrt{16161}}{4}x}" .
Find a typical (specific) solution of the non-homogeneous equation in the form "y_p=Ae^{-x}"
Derivatives of the solution: "\\frac{dy_p}{dx}=-Ae^{-x}" , "\\frac{d^2y_p}{dx^2}=Ae^{-x}"
Substitute those "solutions" into the (**):
"2Ae^{-x}+127Ae^{-x}-4Ae^{-x}=-8e^{-x}"
"2A+127A-4A=-8"
"A=-\\frac{8}{125}"
"y_p=-\\frac{8}{125}e^{-x}" .
Add the typical and the complementary solutions to get the complete solution:
"y=y_0+y_p=C_1e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2e^{\\frac{127+\\sqrt{16161}}{4}x}-\\frac{8}{125}e^{-x}" .
To find "z" substitute "y" into the (*):
"z=\\frac13(C_1\\frac{127-\\sqrt{16161}}{4}e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2\\frac{127+\\sqrt{16161}}{4}e^{\\frac{127+\\sqrt{16161}}{4}x}+\\frac{8}{125}e^{-x}+"
"8(C_1e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2e^{\\frac{127+\\sqrt{16161}}{4}x}-\\frac{8}{125}e^{-x})-5e^{-x} )="
"C_1\\frac{159-\\sqrt{16161}}{12}e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2\\frac{159+\\sqrt{16161}}{12}e^{\\frac{127+\\sqrt{16161}}{4}x}-\\frac{227}{125}e^{-x}"
Answer: "\\begin{cases}\n y=C_1e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2e^{\\frac{127+\\sqrt{16161}}{4}x}-\\frac{8}{125}e^{-x} \\\\\n z=C_1\\frac{159-\\sqrt{16161}}{12}e^{\\frac{127-\\sqrt{16161}}{4}x}+C_2\\frac{159+\\sqrt{16161}}{12}e^{\\frac{127+\\sqrt{16161}}{4}x}-\\frac{227}{125}e^{-x}\n\\end{cases}"
Comments
Leave a comment